CD1d knockout mice exhibit aggravated contact hypersensitivity responses due to reduced interleukin‐10 production predominantly by regulatory B cells. Issue 11 (21st August 2015) - Fjelbye, Jonas; Antvorskov, Julie C.; Buschard, Karsten; Issazadeh‐Navikas, Shohreh; Engkilde, Kåre
Abstract: Conflicting observations have been reported concerning the role of CD1d‐dependent natural killer T (NKT) cells in contact hypersensitivity (CHS), supporting either a disease‐promoting or downregulatory function. We studied the role of NKT cells in CHS by comparing the immune response in CD1d knockout (CD1d KO) and wild‐type (Wt) mice after contact allergen exposure. For induction of CHS, C57BL/6 CD1d KO mice ( n = 6) and C57BL/6 Wt mice ( n = 6) were sensitised with 1% (w/v) dinitrochlorobenzene (DNCB) or vehicle for three consecutive days and subsequently challenged with a single dose of 0.5% DNCB (w/v) on the ears fifteen days later. We demonstrate that CD1d KO mice, as compared with Wt littermates, have more pronounced infiltration of mononuclear cells in the skin (29.1% increase; P < 0.001), lower frequencies of interleukin‐10 + B cells (Bregs ) in the spleen (53.2% decrease; P < 0.05) and peritoneal cavity (80.8% decrease; P < 0.05) and increased production of interferon‐ γ (3‐fold; P < 0.05) after DNCB sensitisation and challenge, which suggests an important regulatory and protective role of CD1d‐dependent NKT cells in CHS in our model, at least in part via regulation of IL‐10 producing Bregs .